Customer perception on last-mile delivery services using Kansei engineering and conjoint analysis: A case study of Indonesian logistics providers - Dian Palupi Restuputri; Ayun Fridawati; Ilyas Masudin (Logistics, 2022)
Background: This article identifies the preferences of the customer of logistics services in Indonesia using the Kansei engineering and conjoint analysis methods. The Conjoint Analysis aims to establish utility scores that represent factors in logistics services. Methods: In this study, 100 respondents from several cities in East Java, Indonesia, are selected to fill out the formal questionnaire. At the same time, 30 respondents are chosen to determine the attributes and level attributes. The analysis to determine attributes, level attributes, and formal questionnaires are assisted by SPSS 25. Sixteen stimuli are generated in this study to be used for a formal questionnaire. In this study, Kansei is used to provide a different perspective to describe the customer service, Including six attributes: delivery services, delivery speed, courier attitude, order information, condition of goods, and warehouse locations. Results: The results show that customers' most preferred attributes are based on the condition of undamaged objects, and the attitude of the courier is vital for users in this study. Conclusions: The most considered instruments by the customer, such as delivery services, delivery speed, courier attitude, order information, condition of goods, and warehouse location.
Keywords: 650; Kansei engineering; conjoint analysis; logistics service; customer preference